Polyol production from waste materials by genetically modified Yarrowia lipolytica. (November 2017) - Rakicka, Magdalena; Biegalska, Anna; Rymowicz, Waldemar; Dobrowolski, Adam; Mirończuk, Aleksandra M.
Highlights: The first study using wastes for efficient polyols synthesis by Y. lipolytica. Two-stage production results in short fermentation time. Raw molasses and crude glycerol promoted low-cost polyols production. Abstract: Sugar alcohols (polyols) are sweeteners with many industrial applications. In this study, a fermentation process of polyol production based on waste substrates – raw industrial molasses and crude glycerol – was tested. The yeast strain Yarrowia lipolytica Wratislavia K1 was genetically modified by overexpression of the Saccharomyces cerevisiae SUC2 gene and overexpression of the native GUT1 gene. This process allowed for sucrose utilization and rapid glycerol assimilation by the engineered strain. In this study, the obtained strain AIB pAD-UTGut1 produced 100.65 ± 3.75 g/l of polyols, with productivity of 1.09 ± 0.9 g/l h and yield of 0.67 ± 0.2 g/g. This is the first study describing efficient polyol production by the modified Y. lipolytica strain from industrial raw molasses and crude glycerol. By process optimization, we established conditions for abundant polyol synthesis from low-value substrates.